Compounds split by silence: the case of Dutch synthetic adjectival compounds - Lipták, Anikó; Cremers, Crit (Nordlyd, 2026)
We describe a novel ellipsis phenomenon attested in Dutch synthetic adjectival compounds, whereby the right part of the compound undergoes ellipsis and the left part gets realised. Such partial realisation of the compound is standardly accompanied by clausal ellipsis of some sort (gapping, sluicing or fragment formation). After inventorising the morphosyntactic properties of the phenomenon, we argue that the ellipsis targeting the right part of the compound is not coordination reduction (Booij 1985), but standard ellipsis. We settle for an account for the facts that is based on the observation that synthetic adjectival compounds in Dutch are not word-level units but syntactic phrases, within which the stranded first part is a syntactic phrase itself. Its phrasehood allows it to undergo A-bar movement out of the compound to form a remnant of clausal ellipsis, while clausal ellipsis needs to be present to allow the affixal second part to be non-realised.